KESANTUNAN BERBAHASA BALI DI DESA SIBEA KECAMATAN LAMPASIO KABUPATEN TOLITOLI - Wukungsenggo, Yolpi; Afifah Istiqomah, Afifah Istiqomah2; Hasan, Haidar; Ikbal; Sherly, Ni Kadek; Afrillia (LPPM Universitas Madako Tolitoli, 2025)
This research is based on the background of language compliance that occurs in Sibea Village which occurs in the process of speaking among Balinese people. The purpose of this study is to describe the form of politeness in Balinese language in Sibea Village, Lampasio District, Tolitoli Regency. This type of research is qualitative research. The subjects of the study were Balinese people living in Hamlet 3 Raharjo, Sibea Village, Lampasio District, Tolitoli Regency.The results of this study show that the principle of politeness in Balinese language in Hamlet 3 Raharjo, Sibea Village, Lampasio District, Tolitoli Regency showed the number of utterances found as many as 31 data. Consists of a maximum of 6 data of wisdom, a maximum of 3 data of generosity, a maximum of appreciation or praise of 6 data, a maximum of simplicity of 3 data, a maximum of agreement of 7 data and a maximum of sympathy of 6 data. These 31 data show compliance with the politeness maxims of the Balinese language. The data was taken from the speech of the Balinese people consisting of teenagers and parents with an age range of 6- 65 years. The types of spceeh Madya Balinese and smooth or Singgih Balinese.